The Influence of Individualism and Collectivism Parenting on Theory-of-Mind Acquisition in Children Aged 3 – 5 - Rusli, Devi; Kuntoro, Ike Anggraika; Handayani, Eko; Nurmina; Arben, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to investigate the influence of parental individualism and collectivism on theory of mind acquisition in children age 3-5 years. Theory of mind (ToM) acquisition was assessed using a ToM scale by Wellman and Liu (2004), and individualism and collectivism parenting was measured with a scale that was developed from Triandis and Gelfand’s individualism-collectivism scale. The ToM scale was administered to 202 children ages 3 – 5 years old/36-71 months (M = 55, SD = 3.253), and the individualism and collectivism parenting scale was administered to their parents. The result of this study showed that individualism and collectivism parenting did not significantly influence children’s ToM (R2 = .012, p > 0.05.). Individualism parenting significantly influenced the acquisition of diverse beliefs (DB) (β = 0.017, p < 0.05), whereas collectivism parenting did not significantly predict the acquisition of the five concepts of ToM.